Hubungan Sikap Ibu Terhadap Motivasi dalam Merawat Anak dengan Autisme di Sekolah Luar Biasa-C Negeri Pembina dan Yayasan Borneo Autisme Therapy Center Banjarmasin Provinsi Kalimantan Selatan Tahun 2013 - Ni Wayan Kurnia; Salasiah Supiyati; Angi Khairunnisa; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2014)
Autism is a severe developmental disorder in children, their development becomes impaired, especially in communication, interaction, and behavior. Role of parents in the treatment of children with autism is the inporter. Mother as one of the parents of children with autism is very important in knowing a child's development. Design used in this study is a cross sectional analytic approach, sample size of 41 people and the purpose of this study was to analyze the relationship between maternal attitudes towards motivation in caring for children with autism. The results showed that there is a relationship between maternal attitudes towards motivation in caring for children with autism. Recommendations for future research is to further analyze other factors that may affect maternal motivation in caring for children with autism.